Representasi Feminisme dalam Video Klip Lagu God is a woman (Analisis Semiotika Roland Barthes) - Carolina Poetiray, Kezia Judith; Alit Suryawati, I Gusti Agung; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2021)
The ability of video clips to represent various kinds of social phenomena is used to create works to influence people's views, one of which is the issue of feminism. Ariana Grande released the music video for her song “God is a woman”, which includes a depiction of feminism. The purpose of this research is to see the representation of feminism in the video clip. This qualitative descriptive study examines data using the concept of video clips as a medium of mass communication, feminism issues, Stuart Hall's representation theory, and Roland Barthes' Semiotics theory. The results showed that the video clip of the song “God is a woman” represents postmodern feminism which is shown by the female character described by Ariana Grande who has freedom like men without trying to dissolve gender differences, who can express herself, who dares to fight patriarchy, and has power over her own body.    Keywords : Feminism, Video Clip, God is a woman, Roland Barthes.